The Titanic - Aaseng, Nathan (San Diego, Calif. : Lucent Books, 1999)
Discusses the design and building of the monster ship the Titanic, its maiden voyage, and what went wrong on the fateful night when it struck an iceberg and sank.
Includes bibliographical references (p. 90-92) and index.
Keywords: Titanic (Steamship) -- Juvenile literature; Titanic (Steamship); Shipwrecks -- North Atlantic Ocean -- Juvenile literature; Shipwrecks